Grenzen und Möglichkeiten linker Stadtpolitik: Eine Erwiderung auf Klaus Lederer - Lebuhn, Henrik (PROKLA. Zeitschrift für kritische Sozialwissenschaft, 2008)
Responding to Klaus Lederer's critique on an earlier article written by the author, the text highlights the preformation of the urban political arena via New Public Management, and looks at the different roles that progressive parties and grassroots movements play under these conditions.